Rapid J2EE(TM) Development : An Adaptive Foundation for Enterprise Applications. - Monnox, Alan (Hewlett-Packard professional books., 2005)
Praise for Rapid J2EE Development "The author provides a good survey of the technologies and approaches for rapid development in the J2EE arena. He touches on all areas that should be of interest to a reader, from design through testing. He illustrates the different phases of rapid development by going into several technologies in depth, and he also lists or otherwise mentions other available technologies. I would recommend this book to anyone looking to get started with developing J2EE applications." -Beth Stearns, Consultant, ComputerEase Publishing "This book has a lot of great material in it. The author really shows his experience in the subject matter. The content is excellent. I haven't seen another book that is as comprehensive or contains as many real-world lessons learned." -Madhu Siddalingaiah, Consultant, SEA Corporation "I think the book does a good job of presenting a set of processes and technologies that enable rapid development. I think this is an extremely useful book, and I would recommend it to others." -Satadip Dutta, Software Engineer, HP "The author skillfully presents a collection of tools, technologies and processes that facilitate rapid development of J2EE applications. I see this book as a valuable addition to any company bookshelf, especially given its broad application across the software lifecycle. It's also quite amazing that a Google search does not reveal any existing publications with this title. This book should neatly fill that hole." -Martin Westacott, Director and Senior Consultant, Solstice Software Limited, U.K. "If you ever needed to put some polish to your J2EE development understanding or would like to move into the role of Senior J2EE Developer, then this is the book for you. The author covers everything you need to take you from design to coding to build process. Along the way he introduces some new valuable 'leading-edge' technologies. All this will leave you with good capabilities to tackle most J2EE projects confidently." -Shane Griggs, J2EE Architect Learn to accelerate J2EE development, from design through testing and beyond. Covers agile development, model-driven architecture, code generation, aspect-oriented programming, test-driven development, and much more. An essential resource for every J2EE developer, project leader, and manager. J2EE is today's premier platform for enterprise-level development, but it's difficult to deliver J2EE solutions as quickly as today's businesses need them. This...